2015
DOI: 10.1039/c5gc01451d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic deep eutectic solvents as water-immiscible extractants

Abstract: Hydrophobic deep eutectic solvents consisting of decanoic acid and various quaternary ammonium salts are presented and evaluated as extractants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
455
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 657 publications
(488 citation statements)
references
References 24 publications
25
455
3
5
Order By: Relevance
“…Furthermore, the elongation of the side chain rightfully leads to decreased densities (thus to less dense systems) probably due to the increased space requirement of the longer side chains. This trend is confirmed by the experimental hydrophobic DES study of Kroon and coworkers …”
Section: Figuresupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the elongation of the side chain rightfully leads to decreased densities (thus to less dense systems) probably due to the increased space requirement of the longer side chains. This trend is confirmed by the experimental hydrophobic DES study of Kroon and coworkers …”
Section: Figuresupporting
confidence: 74%
“…MH studies in DES started when hydrophobic DES were presented and successfully applied in extraction processes . A nanoscale spatial heterogeneity was found from molecular dynamics simulations of acetamide with Li+ClO4- and propionamide with Li+ClO4- .…”
Section: Figurementioning
confidence: 99%
“…This is necessary to evaluate the behavior of hydrophobic DES with water. We have applied the first three techniques in our previous works on the extraction of fatty acids from aqueous solutions using the same DESs reported here 16 and extraction of metal ions with DESs. 20 Therefore, as an extension of our former works, the pH of the water phase after being mixed with the investigated DESs has been measured.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison among DES-1, DES-2, and DES-3 indicated that the extraction yield with DES-1 was maximal. When the HBD/HBA molar ratio decreased from 2 : 1 to 1 : 2, the amounts of HBA increased, and thus resulted in the decrease in viscosity and surface tension, which would enhance their extraction efficiency [25,26].…”
Section: Comparison Of the Extractability Of Dessmentioning
confidence: 99%